Notes and reflections on impedance spectroscopy - Frechero, Marisa Alejandra (2017)
According to the fundamental theory, the interaction ofelectromagnetic field with matter is well described by Maxwell’sequations [1]. The thing is, if we disturb the matter applying analternant potential difference through it a resonance phenomenontakes place. If we capture that response as a signal it is possible tointerpret what is happening inside. And, this word inside is probablythe most attractive thing when we are dealing with alive organisms because we want to study them without damaging them.